Dynamics of Land Use and Land Cover Changes in Dhunat Upazila using Remote Sensing and GIS between 2000 and 2024 - Ali, Mohammad; Rakib, Muhammad Rezaul; Islam, Md. Nurul; Islam, Md. Robiul (The Jahangirnagar Review, 2025)
Land use and land cover (LULC) changes significantly impact environmental sustainability, resource management, and land-use planning. This study analyzes the spatial and temporal dynamics of LULC changes in Dhunat Upazila, Bangladesh, between 2000 and 2024 using Landsat 5 TM (2000) and Landsat 8 OLI (2024) satellite imagery. Supervised Classification with the Maximum Likelihood Classification (MLC) method and Post-Classification Comparison (PCC) were applied to detect LULC transitions over time. The findings reveal a substantial reduction in agricultural land (-14.86 km²) and barren land (-4.96 km²), while vegetation (+16.82 km²) and water bodies (+2.99 km²) expanded. The accuracy assessment reported an overall accuracy of 81.5% (2000) and 84.2% (2024), with kappa coefficients of 81.34 and 84.42, ensuring classification reliability. The primary drivers of LULC transformation include agricultural expansion (22.30%), urbanization (18.70%), riverbank erosion (14.20%), and deforestation (12.40%). These changes indicate a shift towards increased vegetation cover and water body expansion, influenced by conservation measures, hydrological shifts, and socio-economic transformations. The study underscores the need for sustainable land-use policies, adaptive agricultural strategies, and afforestation programs to enhance ecological resilience in riverine floodplains.